The Pricing of Default‐free Interest Rate Cap, Floor, and Collar Agreements - BRIYS, ERIC; CROUHY, MICHEL; SCHÖBEL, RAINER (Journal of Finance, 1991)
ABSTRACT The paper focuses on the valuation of caps, floors, and collars in a contingent claim framework under continuous time. These instruments are interpreted as options on traded zero coupon bonds. The bond prices themselves are used as the underlying stochastic variables. This has the advantage that we end up with closed form solutions which are easy to compute. Special attention is devoted to the choice of the stochastic process appropriate for the price dynamics of the underlying zero coupon bonds.